2018
DOI: 10.3390/su10020299
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructural and Human Factors Affecting Safety Outcomes of Cyclists

Abstract: Abstract:The increasing number of registered road crashes involving cyclists during the last decade and the high proportion of road crashes resulting in severe injuries and fatalities among cyclists constitutes a global issue for community health, urban development and sustainability. Nowadays, the incidence of many risk factors for road crashes of cyclists remains largely unexplained. Given the importance of this issue, the present study has been conducted with the aim of determining relationships between inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 51 publications
1
38
0
1
Order By: Relevance
“…One solution to these problems could be to encourage sustainable transport modes such as cycling. However, for cycling to be widely accepted, good conditions ensuring safety and comfort should be established to minimize stress [1]. Although other means of transport where users are in a protected environment (e.g., vehicles) are subjected to a certain degree of environmental noise, stressful situations experienced by cyclists may be influenced more directly by environmental noise.…”
Section: Introductionmentioning
confidence: 99%
“…One solution to these problems could be to encourage sustainable transport modes such as cycling. However, for cycling to be widely accepted, good conditions ensuring safety and comfort should be established to minimize stress [1]. Although other means of transport where users are in a protected environment (e.g., vehicles) are subjected to a certain degree of environmental noise, stressful situations experienced by cyclists may be influenced more directly by environmental noise.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in the classification power verified for oversampling techniques for both classifier models; however, this is not always regarding the undersampling technique and ROSE. e best results (highlighted in (8) Road Conditions (30) Month (22) Age (17) Oversampling…”
Section: Datasetsmentioning
confidence: 99%
“…Considering the cyclist database for Lisbon, oversampling is the best resampling technique for both classifiers. Besides, this Road Conditions (19) Month (17) Age (14) Month (18) Road Markings (14) Age (14) Road Markings (42) Time (21) Age (19) Age (43) Gender (30) Road Markings (20) explore and compare the results of two supervised classification techniques in order to entify which variables can significantly affect pedestrian and cyclist injury severity when olved in a motor vehicle crash. e three resampling techniques were applied to the datasets, resulting in six different datasets city and the overall perspective.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of public health and safety, identifying bicycling behaviors that increase or decrease crash risk is an important objective. A number of recent studies dealing with bicycling behaviors have focused on risky behavior [1][2][3][4][5][6][7][8][9][10][11], and several of these studies reported associations between engaging in risky behaviors and previous crashes or near-misses [1,2,4,5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%